Research of obstacles in inclusion of forced migrant children in the primary education in Serbia - Golubović, Marija (Sociološki pregled, 2022)
Since 2015, as many as 1.5 million migrants and refugees have passed through Serbia, whereas children account for one quarter of that number. Due to their longer stay in the territory of Serbia, a need has arisen, among other things, to include them in the education system. This research was aimed at determining factors that lead to the creation of obstacles in the inclusion of forced migrant children in primary education in Serbia, as well as during the process of education and, thus, how to overcome those obstacles in practice. Through semi-structured interviews, data were collected about the experience in teaching work with forced migrant children in Primary School “Ljupče Španac” in Bela Palanka. The participants of the research were the teachers of this school who during the academic 2018/19 year for the first time gained experience in working with forced migrant children. The research results show that greater system support is necessary for including forced migrant children in education, while an outstanding obstacle is the language barrier – in communication with children, but also with parents.